Topological Models of Finite Type for Tree Almost Automorphism Groups. (31st October 2016) - Sauer, Roman; Thumann, Werner
Abstract: We show that tree almost automorphism groups, including Neretin groups, satisfy an analogue of the $F_∞$ -finiteness condition in the world of totally disconnected groups: They possess a cellular action on a contractible cellular complex such that the stabilizers are open and compact and the restriction of the action on each $n$ -skeleton is cocompact.